Fluorescence lifetime metabolic mapping of hypoxia‐induced damage in pancreatic pseudo‐islets. Issue 12 (15th October 2020) - Zbinden, Aline; Carvajal Berrio, Daniel A.; Urbanczyk, Max; Layland, Shannon L.; Bosch, Mariella; Fliri, Sandro; Lu, Chuan‐en; Jeyagaran, Abiramy; Loskill, Peter; Duffy, Garry P.; Schenke‐Layland, Katja
Abstract: Pancreatic islet isolation from donor pancreases is an essential step for the transplantation of insulin‐secreting β‐cells as a therapy to treat type 1 diabetes mellitus. This process however damages islet basement membranes, which can lead to islet dysfunction or death. Posttransplantation, islets are further stressed by a hypoxic environment and immune reactions that cause poor engraftment and graft failure. The current standards to assess islet quality before transplantation are destructive procedures, performed on a small islet population that does not reflect the heterogeneity of large isolated islet batches. In this study, we incorporated fluorescence lifetime imaging microscopy (FLIM) into a pancreas‐on‐chip system to establish a protocol to noninvasively assess the viability and functionality of pancreatic β‐cells in a three‐dimensional in vitro model (= pseudo‐islets). We demonstrate how (pre‐) hypoxic β‐cell‐composed pseudo‐islets can be discriminated from healthy functional pseudo‐islets according to their FLIM‐based metabolic profiles. The use of FLIM during the pretransplantation pancreatic islet selection process has the potential to improve the outcome of β‐cell islet transplantation. Abstract : Fluorescence lifetime imaging microscopy (FLIM) is a powerful technique for the screening of pancreatic β‐cell‐composed islets prior transplantation. In our study, FLIM‐based metabolic profiles utilizing the endogenous fluorescence of the coenzymes nicotinamide adenine dinucleotide and flavin adenine dinucleotide enabled the detection of early hypoxia‐induced damages. Glucose‐response was detected noninvasively in β‐cells. The use of FLIM has the potential to improve the outcome of β‐cell islet transplantation to treat type 1 diabetes mellitus.